Tracing Themes of Transhumanism and the Posthuman in Twenty-First Century Rewritings of Mary Shelley’s Frankenstein - von Strokirch,Jacob (2026)
Mary Shelley’s Frankenstein (1818) is one of the most famous works of fiction ever written and thus much has already been said about it. Recent criticism of the novel has identified the presence of transhumanist themes in Victor Frankenstein’s quest to create a new superior species and defeat death. Several thought-provoking retellings of Shelley’s story have been published since the formation of modern transhumanist theory, but no attempt has been made to track the transhumanist theme from the original work to its adaptations. Therefore, this essay aims to uncover what twists modern writers have given this aspect of Frankenstein, covering both Ahmed Saadawi’s Frankenstein in Baghdad (2014) and Jeanette Winterson’s Frankissstein (2019) as well as contemporary transhumanist theory in general. By analysing and comparing the two works through the frame of this theory as well as the original Frankenstein, this essay concludes that both Saadawi and Winterson offer a rejection of typical twentieth and twenty-first century transhumanism and instead embrace a different view - one of human evolution through unity.
Keywords: Frankenstein; Mary Shelley; Frankissstein; Jeanette Winterson; Frankenstein in Baghdad; Ahmed Saadawi; transhumanism; the posthuman